Minocycline inhibition of monocyte activation correlates with neuronal protection in SIV neuroAIDS. - Jennifer H Campbell; Tricia H Burdo; Patrick Autissier; Jeffrey P Bombardier; Susan V Westmoreland; Caroline Soulas; R Gilberto González; Eva-Maria Ratai; Kenneth C Williams (PLoS ONE)
Background Minocycline is a tetracycline antibiotic that has been proposed as a potential conjunctive therapy for HIV-1 associated cognitive disorders. Precise mechanism(s) of minocycline's functions are not well defined. Methods Fourteen rhesus macaques were SIV infected and neuronal metabolites measured by proton magnetic resonance spectroscopy ((1)H MRS). Seven received minocycline (4 mg/kg) daily starting at day 28 post-infection (pi). Monocyte expansion and activation were assessed by flow cytometry, cell traffic to lymph nodes, CD16 regulation, viral replication, and cytokine production were studied. Results Minocycline treatment decreased plasma virus and pro-inflammatory CD14+CD16+ and CD14(lo)CD16+ monocytes, and reduced their expression of CD11b, CD163, CD64, CCR2 and HLA-DR. There was reduced recruitment of monocyte/macrophages and productively infected cells in axillary lymph nodes. There was an inverse correlation between brain NAA/Cr (neuronal injury) and circulating CD14+CD16+ and CD14(lo)CD16+ monocytes. Minocycline treatment in vitro reduced SIV replication CD16 expression on activated CD14+CD16+ monocytes, and IL-6 production by monocytes following LPS stimulation. Conclusion Neuroprotective effects of minocycline are due in part to reduction of activated monocytes, monocyte traffic. Mechanisms for these effects include CD16 regulation, reduced viral replication, and inhibited immune activation.